60 Transradial access for complex chronic total occlusion – 6 year study demonstrates similar success rates to transfemoral access with decreased complications. (October 2018) - Hughes, D; Hafiz, H; Traynor, B; Foley, D; Kennedy, M
Abstract : Introduction: International registry data audits for centres performing CTO (chronic total occlusion) PCI consistently report a success rate of approximately 75% to 85%, with the vast majority of centres using femoral access. TFA is used due to the belief that TRA might compromise catheter support and certain device utilization. To investigate whether success rates, and other measures of effectiveness such as time taken per procedure and contrast use, are affected by access point we have performed a retrospective study of all consecutive CTO PCI over a 6 year period. Methods: We performed a retrospective analysis of all consecutive CTO procedures in two institutions from June 2010 until December 2016. During this period we reviewed 270 cases of CTO from the two hospitals; one of which was a large public teaching hospital and the other was a private institution. For the purposes of this study we only included those CTO lesions with a TIMI flow of 0, which were present for more than 3 months, longer than 20 mm and required bilateral access utilizing hybrid techniques. We subsequently divided the cases by access point into transradial and transfemoral groups with a successful reopening was defined as a restoration of TIMI 3 flow and <50% residual stenosis. Results: During the period of our study we identified 270 cases of complex PCI CTO involving 233 patients. The average age of patients was 68 years, the majority were men (86%), 141 (61%) had hypertension, 54 (23%) had diabetes mellitus, 119 (51%) had dyslipidaemia, 90 (39%) had had a previous myocardial infarction and 41 (18%) were current smokers. Table 1 shows the results from our study divided by access site. TRA was used in the majority of our cases at 58% with no major differences between the two cohorts, apart from a higher number of previously failed cases being attempted with TFA. The overall success rate with TRA was 89% versus 77% for TFA cases. The TRA group had lower procedure times (2 hours versus 3 hours) and lower contrast use (378 ml versus 422 ml) than the TFA group. There was a lower complication rate in the TRA group 6.4% versus 14% especially in regards to contrast induced nephropathy and vascular complications. Conclusion: The main finding from our study is that it is feasible to reopen the majority of complex CTO cases with TRA and it can be adopted as a default strategy. Using TRA in the majority of our cases did not impact on success rates, procedure time nor contrast used. The baseline characteristics of the patients were very similar indicating that the TRA is suitable for the majority of patients. Our study adds further evidence that TRA is safe and effective for the majority of complex CTO cases with a reduction in complication's and improved patient outcomes.